The Religion-Based Fun School Model Perspective of Peter L. Berger: (Studies at MIN 2 and SDK Sang Timur Sumenep) - Iwan Kuswandi; Ahmad Yasid (EDUCARE: Journal of Primary Education, 2022)
This paper describes the externalization, objectivity, and internalization of schools of elementary fun school. This Islamic Elementary School (MIN 2) represents the Islamic schools, and the Christian Elementary School (SDK) Sang Timur Sumenep school represents Christian schools. This study used a case study to collect observational data, interviews, and documentation; the results of the research findings were analyzed using The Social Reality Construction of Peter L Berger's theory. The conclusion from the discussion above is the form of externalization carried out in the two schools above regarding a positive school culture. In contrast, in terms of objectivity, it can be seen from the excellent running in terms of Organizational Structure and Work Procedures (SOTK) there is clarity of discipline for both teachers and students. In terms of internalization, the moral and personality aspects of students are more excellent than the two schools. Fokus tulisan ini untuk mendeskripsikan bagaimana bentuk eksternalisasi, objektivasi dan internalisasi sekolah menyenangkan di sekolah MIN 2 Sumenep yang merupakan sekolah representasi agama Islam, dan sekolah SDK Sang Timur Sumenep, yang merupakan representasi sekolah Kristen. Penelitian ini menggunakan studi kasus, dengan metode pengumpulan data observasi, wawancara dan dokumentasi, hasil temuan penelitian dianalisa menggunakan teori Konstruksi Realias Sosial Peter L Berger. Kesimpulan dari pembahasan di atas, bahwa bentuk eksternalisasi yang dilakukan pada kedua sekolah di atas, dalam hal kultur sekolah yang positif, sedangkan dalam hal objektivasi terlihat dari berjalannya dengan baik dalam hal Struktur Organisasi dan Tata Kerja (SOTK), adanya kejelasan tata tertib baik bagi guru maupun siswa. Dalam hal internalisasi, aspek moral dan aspek kepribadian siswa sangat baik yang dimiliki oleh kedua sekolah tersebut.